Molecular cloning and sequence analysis of canine acidic ribosomal phosphoprotein P0 cDNA - Canatan, H; Lin, YC (Harwood Acad Publ Gmbh, 2000)
Acidic ribosomal phosphoprotein PO has been widely used as an estradiol-independent housekeeping gene. Expression of acidic ribosomal phosphoprotein PO in canine prostate was detected and canine specific cDNA was cloned. Total cellular RNA was isolated from normal young (5 month-old) canine prostate tissue. Total cDNAs were synthesized from total cellular RNAs by reverse transcription assay. Primers used in polymerase chain reaction were designed from published human ARP0 cDNA sequences and utilized to amplify 562 base-pair (bp) canine acidic ribosomal phosphoprotein PO cDNA. Nucleotide sequences of canine ARP0 cDNA clones were determined on both strands. Canine ARP0 cDNA and their deduced amino acid sequences share very high homology to ARP0 orthologs from other vertebrate species including human, mouse, rat, chicken, and bovine.
Keywords: acidic ribosomal phosphoprotein P0; canine; cDNA; cloning; prostate